2012
DOI: 10.1002/jae.2298
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive look at financial volatility prediction by economic variables

Abstract: SUMMARY We investigate whether return volatility is predictable by macroeconomic and financial variables to shed light on the economic drivers of financial volatility. Our approach is distinct owing to its comprehensiveness: First, we employ a data‐rich forecast methodology to handle a large set of potential predictors in a Bayesian model‐averaging approach and, second, we take a look at multiple asset classes (equities, foreign exchange, bonds and commodities) over long time spans. We find that proxies for cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
157
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(167 citation statements)
references
References 87 publications
10
157
0
Order By: Relevance
“…A subject of particular interest concerns the joint-behavior of volatility and the economy with a special emphasis on their lead-lag pattern and on the cyclical behavior of stock market volatility. Many contributions, including Hamilton and Lin (1996), Perez-Quiros and Timmermann (2000), Christiansen et al (2012), Corradi et al (2013), and Paye (2012), reported evidence of the counter-cyclical behavior of the long-run market volatility. Hence, if the economy shrinks, stock market volatility is expected to increase in response to concerns about future market conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A subject of particular interest concerns the joint-behavior of volatility and the economy with a special emphasis on their lead-lag pattern and on the cyclical behavior of stock market volatility. Many contributions, including Hamilton and Lin (1996), Perez-Quiros and Timmermann (2000), Christiansen et al (2012), Corradi et al (2013), and Paye (2012), reported evidence of the counter-cyclical behavior of the long-run market volatility. Hence, if the economy shrinks, stock market volatility is expected to increase in response to concerns about future market conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For the i-th stock, the observed value of JU MP at t is denoted by jump i,t ; we checked that the jump i,t series has evident peaks in periods of financial turmoil (the estimated jumps series are available on request). For reasons of consistency, when we analyse FPC, we compute jump t as the first principal component of jump i,t , for i = 1, ..., 16.…”
Section: Realized Volatilities and Conditioning Variablesmentioning
confidence: 99%
“…For instance, Christiansen et al [16] predicted the asset return volatility using macroeconomic and financial variables in a Bayesian model averaging framework. They considered several asset classes, such as equities, foreign exchange, bonds and commodities, over long time spans and found that economic variables provide information about future volatility from both an in-sample and an out-of-sample perspective.…”
Section: Introductionmentioning
confidence: 99%
“…However, the focus has mostly been on univariate models, such as the GARCH class of models (Engle 1982, Bollerslev 1986), or univariate …ltering methods that use realized high-frequency volatility (Barndor¤-Nielsen andShephard 2002, Andersen et al 2003). A much smaller literature has, like us, looked directly at the information in other economic and …nancial variables concerning future volatility (Schwert 1989, Christiansen, Schmeling, and Schrimpf 2012, Paye 2012, Engle, Ghysels, and Sohn 2013.…”
Section: Literature Reviewmentioning
confidence: 99%